2022
DOI: 10.1108/k-02-2022-0234
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capital, corporate social responsibility and sustainable competitive performance of small and medium-sized enterprises: mediating effects of organizational innovation

Abstract: PurposeThis study aims to explore the mechanism by which intellectual capital and corporate social responsibility (CSR) influence the sustainable competitive performance of small and medium-sized enterprises (SMEs), with the mediating role of organizational innovation in an emerging economy.Design/methodology/approachThe data collection was conducted through a survey completed by 208 owners and top managers operating in the service, trading and manufacturing sector SMEs, positioned within twin cities of Pakist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 92 publications
2
36
0
Order By: Relevance
“…Therefore, SMEs with good social and environmental programs gain a positive reputation in the market, ultimately improving their financial performance (Agyemang & Ansong, 2017). This result supports previous studies that found a positive relationship between social and environmental responsibility practices and the financial performance of SMEs (Ahmad et al, 2022;Bahta et al, 2021;Bartolacci et al, 2020).…”
Section: Sustainability Performance and Financial Performancesupporting
confidence: 86%
See 3 more Smart Citations
“…Therefore, SMEs with good social and environmental programs gain a positive reputation in the market, ultimately improving their financial performance (Agyemang & Ansong, 2017). This result supports previous studies that found a positive relationship between social and environmental responsibility practices and the financial performance of SMEs (Ahmad et al, 2022;Bahta et al, 2021;Bartolacci et al, 2020).…”
Section: Sustainability Performance and Financial Performancesupporting
confidence: 86%
“…In developing countries, concern for the environment also opens up opportunities for SMEs to win more contracts, especially with customers who are aware of the environment (Ikram et al, 2020). Previous studies have also confirmed a positive relationship between social and environmental responsibility practices and the financial performance of SMEs (Ahmad et al, 2022;Bahta et al, 2021;Bartolacci, Caputo, & Soverchia, 2020). Thus, the third hypothesis is formulated as follows:…”
Section: Sustainability Performance and Financial Performancementioning
confidence: 94%
See 2 more Smart Citations
“…On the basis of the above, in the relationship between CSR and performance, the mediating role of innovation is obvious. The links between CSR and company performance are explained by intangible resources, which include innovation (Ahmad et al, 2022). For companies to increase their performance, they need the capabilities that innovation brings to them (El-Gammal et al, 2018).…”
mentioning
confidence: 99%